Pengurusan permintaan air oleh pihak berkuasa tempatan daerah Johor Bahru - Nor Azhar, Nur A'in Ilani (2016)
Malaysia aspires to achieve the developed nation status by 2020. In order to achieve this vision, she would need to address a wide variety of issues. One of which pertains to the quality of life and well-being of its citizenry. The efficient management and provision of treated water to the population is widely recognized as an important indicator to the quality of life and well-being. In addition, the effective transmission and distribution of treated water is a stimulus for local economic activities. Therefore, a study on the management of water demand was carried out in three municipalities areas within the District of Johor Bahru, namely, the Johor Bahru City Council, the Johor Bahru Tengah Municipal Council and the Pasir Gudang Municipal Council. The functions, water comsumption, problems and issues of water management, and implication to water management of the three local authorities were the focus of the study. Data for the study were collected from primary and secondary sources and descriptive statistics was used for the analysis of the data. The analysis consisted of three elements, namely, the local authority as the regulator, Syarikat Air Johor (SAJ) as the water provider and the operators of public, social, and recreational facilities and amenities as the water consumers (traders of market and food court, public toilets and hall operators). Socio-economic factors, population of the community, water quality, land use types, climate and sanitary facilities (toilet) influence water consumption. The study also found that the function pertaining to water management within the local authorities is unclear. There are also weaknesses in the management of water by the local authorities. Hence, there is a need to review the water management system of both, the local authorities and SAJ .